2010
DOI: 10.1073/pnas.0913191107
|View full text |Cite
|
Sign up to set email alerts
|

Abasic sites and strand breaks in DNA cause transcriptional mutagenesis in Escherichia coli

Abstract: DNA damage occurs continuously, and faithful replication and transcription are essential for maintaining cell viability. Cells in nature are not dividing and replicating DNA often; therefore it is important to consider the outcome of RNA polymerase (RNAP) encounters with DNA damage. Base damage in the DNA can affect transcriptional fidelity, leading to production of mutant mRNA and protein in a process termed transcriptional mutagenesis (TM). Abasic (AP) sites and strand breaks are frequently occurring, sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…However, in nonreplicating cells, AP sites are also the source of transcriptional mutagenesis (TM). In this respect, Clauson et al (49) reported that nonreplicating cells of a ⌬nfo exoA E. coli strain increased the levels of TM in response to the presence of AP sites, single-strand breaks, and oxidized bases such as 8-oxo-G. In B. subtilis, a variant of this process has been shown to be involved in adaptive mutagenesis and has been termed transcription-associated mutagenesis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…However, in nonreplicating cells, AP sites are also the source of transcriptional mutagenesis (TM). In this respect, Clauson et al (49) reported that nonreplicating cells of a ⌬nfo exoA E. coli strain increased the levels of TM in response to the presence of AP sites, single-strand breaks, and oxidized bases such as 8-oxo-G. In B. subtilis, a variant of this process has been shown to be involved in adaptive mutagenesis and has been termed transcription-associated mutagenesis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…A s one of the most frequent lesions in the genome, DNA abasic (AP) sites are derived from either spontaneous hydrolysis of the glycosidic bonds, often as a result of alkylation or oxidation of purines, or the enzymatic removal of modified bases by glycosylase enzymes in the base excision repair (BER) pathway (1)(2)(3). Failure to repair AP sites poses a severe challenge to polymerases and also leads to strand breaks, DNA cross-links, and transcriptional mutations, resulting in cellular dysfunction (1,2,4).…”
Section: Alpha-hemolysin | Crown Ethers | Single-molecule Detection |mentioning
confidence: 99%
“…1 These authors contributed equally to this work. specific post-translational modifications, oligomeric state and/or subcellular localization, which determine the binding partners (Copley, 2012;Sirover, 2005Sirover, , 2011. Each function requires binding into specific protein complexes.…”
Section: Introductionmentioning
confidence: 99%